Self-rehearsal in the beginning orchestra classroom - Burke, Lauren (Kansas State University, 2023)
For my project, I created a series of beginning orchestra lessons that focused on breaking a piece of music into learnable sections, brainstorming effective rehearsal strategies, creating a rehearsal plan, and rehearsing with peers. The first lesson focuses on analyzing a short excerpt of music. As a class, we broke an example excerpt into four learnable sections: key signature identification, rhythm practice, measure-by-measure practice, and playing through the whole excerpt. Following this, students broke into small groups and repeated the process without teacher intervention. In the second lesson, students brainstormed previously successful rehearsal strategies. They then taught themselves an excerpt of music and were asked to create a rehearsal plan to teach their peers. In lesson three, students executed their rehearsal plans. Afterward, we reflected as a class on what went well and what needed improvement in their rehearsals. Overall, this series of lessons was a successful introduction to self-rehearsal. Students excelled at breaking their excerpts into sections for each other. They were also able to hear when their peers were making mistakes but struggled to fix the problems. Students concluded that they need to work on giving more positive feedback and collaborating as a team. During my time in Kansas State University’s Master of Music program, I recognized that my students greatly relied on teacher-led rehearsal to learn their music and improve their ensemble. A development in my teaching has been to help students break down their music into learnable, focused sections. I have also developed my lessons to include student-led error detection and peer feedback. In the classroom, this is shown through increased small group work, encouraging feedback between sections of the orchestra, and additional questions to students to encourage error detection. As a result of these developments, I have noticed my students are learning notes and rhythms more quickly and communicating better with each other.
Keywords: Student led learning; Peer rehearsal; Music education; Orchestra